'Creative destruction': States, identities and legitimacy in the Arab world. (May 2014) - Anderson, Lisa
In the modern Middle East, the public institutions associated with the internationally recognized states of the region are rarely viewed as trustworthy or reliable. Born in the demise of the Ottoman Empire, midwifed by European imperial powers who paid lip service to the development of the inhabitants, and nurtured in the cold war by superpowers largely indifferent to the well-being of the peoples of the region, the existing states came to be associated with expectations of welfare provision and structures of accountability that privileged external actors over local interests. In the absence of public institutions that responded to and represented local interests, people organized around those still vibrant alternative forms of community that existed – the exchange networks of informal economies or the kinship systems of extended families and the ethnic and religious communities of language, sect and confession – and sometimes they reorganized and reinterpreted these identities to supplement and ultimately supplant the failing states in which they found themselves.